Prevalence of MBL producing pseudomonas aeruginosa in various clinical specimens in tertiary care hospital, Karimnagar - Dr. Amar C. Sajjan; Mr. Sachin R.Gurnule; Dr. B. Aparna (Tropical Journal of Pathology and Microbiology, 2019)
Aim: To find the prevalence of MBL Producing Pseudomonas aeruginosa from various clinical specimen. Material and Methods: A total 114 cases from which Pseudomonas aeruginosa has been isolated from Swab, Urine, pus, Sputum, Bal, Foley’s catheter, E.T. Secretion received from various clinical departments. The study was carried outovera period of Six months. The isolates were tested by IPM-EDTA Combined Disc Test (CDT) and Imipenem-EDTA double disc synergy test (DDST). Descriptive statistics and chi-square is used with the help of MS Excel and SPSS Version 25 Results: Among 114 Pseudomonas aeruginosa isolated from various clinical specimens, 16 (14.03%) imipenem-resistant Pseudomonas isolates. Out of 16 IPM resistant, 15(93.75%) were positive for MBL by CDT-IPM method and 11 (68.75%) were positive by Imipenem-EDTA (DDST) method, respectively. Conclusion: Increase in the resistant pattern of antibiotics can lead to increased morbidity, mortality and economic burden on patients. So it is necessary to detect MBL producing Pseudomonasaeruginosa by simple and effective methods.